2013
DOI: 10.1159/000342575
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Clinical Aspects of GHRH Receptor Mutations

Abstract: The growth hormone (GH)-releasing hormone (GHRH) receptor (GHRHR) belongs to the G protein-coupled receptor family. It binds GHRH resulting in somatotroph cell proliferation and stimulation of GH secretion. Mutations in the gene encoding for GHRHR (GHRHR, OMIM No. 139191) are being reported with increasing frequency in familial isolated GH deficiency. To date, the reported GHRHR mutations include eight missense, seven splice, three microdeletions, and two non-sense mutations. One promoter mutation has also bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…MRIs from adults and children of Itabaianinha kindred show obvious anterior pituitary hypoplasia (APH) (33), as it had been previously shown in 4 adult individuals from the Sindh kindred (17). APH is not due to reduction of cranial volume (33).…”
Section: Pituitary Magnetic Resonance Imaging (Mri)mentioning
confidence: 86%
See 1 more Smart Citation
“…MRIs from adults and children of Itabaianinha kindred show obvious anterior pituitary hypoplasia (APH) (33), as it had been previously shown in 4 adult individuals from the Sindh kindred (17). APH is not due to reduction of cranial volume (33).…”
Section: Pituitary Magnetic Resonance Imaging (Mri)mentioning
confidence: 86%
“…The binding of GHRH causes conformational changes, resulting in the activation of the G s α subunit, stimulation of the membrane-bound adenylyl cyclase, increase of intracellular cyclic adenosine monophosphate (cAMP) and activation of protein kinase A (PKA) pathways. This translocates to the nucleus and phosphorylates the transcription factor cAMP-response element-bindingprotein (CREB) causing the transcription of GH through binding to response elements in the target genes promoter region (17).…”
Section: Understanding the Modelmentioning
confidence: 99%
“…This is, however, not the case for GHRHR mutations. Indeed, the 21 GHRHR disease-causing mutations identified worldwide correspond mainly to case reports (reviewed in Corazzini & Salvatori, 2013), and according to the very rare studies performed in cohorts of patients with IGHD (Alatzoglou et al, 2009;Graaff et al, 2009;Birla et al, 2016;Desai et al, 2013), the estimated contribution of GHRHR mutations to IGHD ranges from 0% to 15% (Graaff et al, 2009;(Desai et al, 2013). In addition, all (Desai et al, 2013) or several families with an identified GHRHR defect were found to carry the p.(E72*) mutation, which results from a founder effect (Wajnrajch et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, LOI of IGF-II gene has been identified as an individual risk factor for developing colorectal carcinoma and, more recently, with poor prognosis of patients with oesophageal squamous cell carcinoma [2,11,62,63]. LOI can be assayed with a DNA-based blood test, and it has been proposed as a predictive marker of an individual's risk for colorectal cancer [2,11,62].…”
Section: Epidemiological Datamentioning
confidence: 99%